Effect of Adding Local Microorganisms in Pineapple Skin (Ananas comosus l. merr) on NPK Levels in The Manufacture of Liquid Compost Based on Tofu Waste - Shaleha, Risda; Junaidi, Junaidi; Pahruddin, Muhammad; Arifin, Arifin (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2023)
Tofu industry liquid waste can be used as a base ingredient in making liquid compost. Liquid compost is made from liquid organic materials/waste by adding a compost activator. One effective activator is local microorganisms (MOL) derived from the fermentation of easily found materials, which decompose organic compounds and can substitute for the EM-4 decomposer. This research aims to determine the effect of adding pineapple peel MOL on the N, P, and K levels of liquid compost based on tofu waste. This experimental research used a Pretest-Posttest with Control Group design. The population and sample were liquid waste from the Dinanti Banjarbaru Tofu Factory. Data analysis utilized the Kruskal-Wallis’s test and simple regression test. Results showed that adding pineapple peel MOL increased N, P, and K levels in liquid compost made from tofu waste. The optimal dose for adding pineapple peel MOL has not been established, but a 200 ml dose showed a statistically significant difference. Pineapple peel MOL can be used as a decomposer to create liquid compost from tofu waste as a substitute for EM-4. However, additional organic materials are needed to enhance the N, P, and K nutrients to meet quality standards. Future research should explore combining starter/decomposer compositions with organic materials to achieve optimal liquid organic fertilizer quality according to compost quality standards.